A representação publicitária de idosos utilizando dispositivos móveis: uma análise da velhice retratada na propaganda brasileira - Brisolara, Cristina Brahm Cassel (2018)
The growth of elderly population in Brazil since 2005 has promoted a series of discussions about it. The growing demand of this public for technological devices awakens the attention of advertising that recognizes its consumption potential, but still bumps into some narratives based on stereotyped characteristics that represent the elderly as displaying either fragile or jovial behavior. The search for a cohesive and creative speech appears to be the challenge to represent the elderly in the actual context. The present investigation addresses the representation of elderly people in advertising utilizing mobile devices broadcasted by open television, in the moment that the issue of the third age represents an important field of studies and debates in the social aspect, at the same time that this population becomes a relevant consumption segment for the market. The investigated issue involves exploring what is the image of the elderly portrayed in advertising narratives when utilizing mobile devices and how these representations reinforce the maintenance of stereotypes associated with aging. The corpus is composed by two advertising pieces that integrate the campaigns of the brands “OLX classificados online” and “Itaú Unibanco”, being them, respectively, “Vovô Radial – Headphone – OLX” and “Chá Digitau: App Itaú”, broadcasted on Brazilian open television in 2015 and 2016. The objectives of this study were to analyze the relation between third age utilizing mobile devices and the discursive practices present in advertising pieces, to investigate the role of advertisement in the maintenance of stereotypes, as well as to identify the advertising importance on the elderly individual’s identity development in the contemporary Brazilian scenario. The research is descriptive regarding its objectives and employed speech analysis of the advertising material, supported by the concepts of Dominique Maingueneau. The data collected is qualitative. The bibliographical review employs Stuart Hall’s, Serge Moscovici’s and Édison Gastaldo’s reflections.